2016
DOI: 10.3354/aei00211
|View full text |Cite|
|
Sign up to set email alerts
|

Temporal variation in sea trout Salmo trutta life history traits in the Erriff River, western Ireland

Abstract: The demographic and life history characteristics of sea trout Salmo trutta L. populations can be changed by a range of pressures in both freshwater and marine environments. Few long-term monitoring programmes are in place to assess temporal change in population dynamics. We analysed a 20 yr time series (1985−2004) using 15 sea trout population response variables in the Erriff River, western Ireland. Over this period, when time was considered as a categorical variable comprising 4 sequential periods of 5 yr, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…In inland waters, the mean length of fish in the catch or assemblage has also been identified as the simplest and most direct indicator of the state of a multispecies fishery (Welcomme, 1999). LBI are assumed to reflect the impacts of size-selective fishing pressure (Froese, 2004;Rochet & Trenkel, 2003;Shin, Rochet, Jennings, Field & Gislason, 2005), but may capture other processes, for example, sea lice infestation of sea trout (Gargan, Kelly, Shephard & Whelan, 2016), that can also curtail size distribution.…”
Section: Length-based Methods-indicatorsmentioning
confidence: 99%
“…In inland waters, the mean length of fish in the catch or assemblage has also been identified as the simplest and most direct indicator of the state of a multispecies fishery (Welcomme, 1999). LBI are assumed to reflect the impacts of size-selective fishing pressure (Froese, 2004;Rochet & Trenkel, 2003;Shin, Rochet, Jennings, Field & Gislason, 2005), but may capture other processes, for example, sea lice infestation of sea trout (Gargan, Kelly, Shephard & Whelan, 2016), that can also curtail size distribution.…”
Section: Length-based Methods-indicatorsmentioning
confidence: 99%
“…All fish were checked weekly for morphological indicators of smolting from March to June in each of 2017 and 2018, the period corresponding to the natural migratory period in the wild for this population (Gargan et al, ). Wild smolts typically migrate out of the Erriff system aged between 1+ and 4+, with the large majority doing so aged 2+ or 3+ (approximately equal numbers of each; Gargan et al, ). Smolting is a precursor to downstream migration in several salmonines, and comprises a number of morphological, behavioural and physiological changes.…”
Section: Methodsmentioning
confidence: 99%
“…Immature fish (unconfirmed sex at the time of sampling) were later genotyped to determine genotypic sex using a microsatellite sex marker. The natural spawning period for the wild population‐of‐origin is in late autumn/early winter, and the migratory period is in the spring (Gargan et al, ). Since freshwater maturation generally precludes migration in brown trout (Dȩbowski & Dobosz, ; Dellefors & Faremo, ; Jonsson, ), any fish showing signs of maturing without having migrated to sea are considered to be on a non‐anadromous trajectory, while smolts which undertake marine migrations are immature.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that an increase in marine mortality and a reduction in sea growth due to lice or other factors affecting trout in the marine environment can result in a population shift in lifehistory strategy (Thorstad et al 2015). Gargan et al (2016) showed significant changes in quantitative life-history traits in the trout population in the Erriff River, western Ireland, after the establishment of salmon farming in the local estuary. These changes included a reduction in the number and size of trout kelts, the estimated number of eggs deposited, the sea trout rod catch, the proportion of older (1+ and 2+ sea age) fish and the frequency of repeat spawners.…”
Section: Consequences For Populationsmentioning
confidence: 99%